2006
DOI: 10.1080/13642530600878048
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in the UK: Results of a survey of registrants of the United Kingdom Council for Psychotherapy

Abstract: The United Kingdom Council for Psychotherapy (UKCP) was formed to provide a professional body for all psychotherapists in the UK. It maintains a register of trained practitioners who abide by the ethical standards ratified by UKCP, which includes psychotherapists working in all the modalities recognized by UKCP irrespective of their primary professional training. In the absence of statutory registration, there is no fully representative list of UK psychotherapists, but the UKCP register is probably the nearest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…The proportion of gender varies among countries; some are dominated by women (e.g. the UK, Canada, Australia, Argentina, China, India; [ 11 16 ]; some by men (New Zealand, South Korea; [ 14 , 17 ]; and in some the proportions are relatively equal (Spain, Germany, Switzerland, Norway; [ 18 20 ]. However, even in countries in which the profession is dominated by women, the proportions are smaller than in Poland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of gender varies among countries; some are dominated by women (e.g. the UK, Canada, Australia, Argentina, China, India; [ 11 16 ]; some by men (New Zealand, South Korea; [ 14 , 17 ]; and in some the proportions are relatively equal (Spain, Germany, Switzerland, Norway; [ 18 20 ]. However, even in countries in which the profession is dominated by women, the proportions are smaller than in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…The results from other studies show that there are countries with younger populations of therapists (e.g. South Korea – 34, China – 37, Argentina – 37 [ 17 ]; [ 12 , 16 ]), but in most of the surveyed countries the age of the therapists is higher (Spain, Germany, Switzerland, Norway, India, New Zealand, [ 14 , 15 , 18 20 ]; in some exceeding even 50 years (USA, Canada, UK, Australia; [ 11 , 13 , 14 , 21 ]. The average age above 50 may reflect the fact that in those countries most people enter the profession later in life as a second career, which probably occurs rarely in Poland; for example, in a survey conducted among psychotherapists in the UK, 95 % of respondents had another profession prior to psychotherapy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In einer zus ä tzlichen Auswertung bez ü glich Gruppenunterschiede hinsichtlich Geschlecht oder Alter der Therapeuten ergaben sich keine signifi kanten Unterschiede. [14] . Insofern ist davon auszugehen, dass die erhobene Stichprobe repr ä sentativ f ü r die Verh ä ltnisse der psychotherapeutischen Versorgung in M ü nchen ist.…”
Section: Problembereiche Der Therapieunclassified
“…International surveys of practitioners have demonstrated that these techniques and the beliefs that underlie them were common in the 1990s, and are still common now (Poole, Lindsay, Memon, & Bull, 1995;Tantam, 2006;Thayer & Lynn, 2006).…”
mentioning
confidence: 98%